Comparative Analysis of the Marginal Fit and Internal Adaptation of CAD-CAM-Fabricated Versus Conventionally Fabricated Ceramic Crowns: A Systematic Review - Mohammed Ibrahim Mathar (Journal of Pharmacy and Bioallied Sciences)
This systematic review compared the marginal fit and internal adaptation of ceramic crowns and fixed dental prostheses (FDPs) fabricated using CAD-CAM technology versus conventional methods. A literature search from 2000 to 2024, following PRISMA guidelines, identified relevant studies. Three studies with a total of 60 patients were included, evaluating both marginal fit and internal adaptation of crowns made using CAD-CAM and conventional techniques. Overall, CAD-CAM-fabricated crowns exhibited smaller marginal discrepancies and better internal adaptation, although the differences were not statistically significant. The findings suggest that CAD-CAM technology may improve the fit of ceramic crowns and FDPs, but variations in study outcomes emphasize the impact of factors like material choice and fabrication methods.